2021
DOI: 10.3389/fcell.2021.647058
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′-Nucleotidase (CD73) Regulates the Survival of CD8+ T Cells

Abstract: Ecto-5′-nucleotidase (CD73) is an enzyme present on the surface of tumor cells whose primary described function is the production of extracellular adenosine. Due to the immunosuppressive properties of adenosine, CD73 is being investigated as a target for new antitumor therapies. We and others have described that CD73 is present at the surface of different CD8+ T cell subsets. Nonetheless, there is limited information as to whether CD73 affects CD8+ T cell proliferation and survival. In this study, we assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Also, adenosine production in the tumor environment, generally considered immunosuppressive, has been shown to also support anti-tumor responses, probably by maintaining IL-7R expression and improving T cell survival ( Cekic and Linden, 2014 ). Rosemblatt et al (2021) have shown that adenosine supports homeostatic proliferation in a lymphopenic environment through upregulation of IL-7R, while inducing cell death in antigen-specific responses through inhibiting IL-2R and BCL2. Finally, CD73 may protect T cells by cleaving AMP and preventing stimulation of P1 receptors ( Rittiner et al, 2012 ; Saze et al, 2013 ), while the generated adenosine is deaminated by adenosine deaminase (ADA) recruited by CD26.…”
Section: Discussionmentioning
confidence: 99%
“…Also, adenosine production in the tumor environment, generally considered immunosuppressive, has been shown to also support anti-tumor responses, probably by maintaining IL-7R expression and improving T cell survival ( Cekic and Linden, 2014 ). Rosemblatt et al (2021) have shown that adenosine supports homeostatic proliferation in a lymphopenic environment through upregulation of IL-7R, while inducing cell death in antigen-specific responses through inhibiting IL-2R and BCL2. Finally, CD73 may protect T cells by cleaving AMP and preventing stimulation of P1 receptors ( Rittiner et al, 2012 ; Saze et al, 2013 ), while the generated adenosine is deaminated by adenosine deaminase (ADA) recruited by CD26.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of CD8 + T cells by differentiation status revealed that A 2A R expression was modestly but significantly higher within the CD69 + SLAMF6 + precursor exhausted subset. This is intriguing given previous studies have indicated that A 2A R signaling is required for the maintenance of naïve cells, partly due to its ability to upregulate IL-7R expression 16 , 29 , 46 , 47 . Whether A 2A R signaling is required for the maintenance and/or expansion of CD69 + SLAMF6 + precursor exhausted CD8 + T cells within tumors remains to be determined but is one potential mechanism by which A 2A R signaling may actually promote a favorable differentiation status for responses to immune checkpoint blockade in some contexts.…”
Section: Discussionmentioning
confidence: 95%
“…Signaling through the adenosine receptor (A 2A R) can prevent TCR-induced downregulation of CD127 (IL-7R), which is found on memory precursors and can promote their survival 31,42 . Thus, CD73 on memory T cells could serve as a continuous source of adenosine, which signals through A 2A R and supports survival 43,44,45 . Furthermore, human circulating memory CD73+ CD4+ T cells have increased expression of pro-survival genes as well as reduced propensity to undergo apoptosis, further emphasizing the functional role of CD73 in memory T cell survival 46 .…”
Section: Discussionmentioning
confidence: 99%